An Overview of Early Modern Missionary Dictionaries of Konkani and Marathi - Pär Eliasson (Orientalia Suecana)
This article provides an overview of missionary dictionaries of Konkani and Marathi compiled in the sixteenth and seventeenth centuries. To give an idea of the linguistic landscape in which the dictionaries were compiled, the article begins by sketching the language situation in early modern western India, mainly from the viewpoint of early modern European lexicographers and grammarians in India. The second part of the article provides an overview of extant and nonextant dictionary manuscripts and their editions.